The Berkut - Heywood, Joseph (Lyons Press, 2015)
Begins at dusk as SS Colonel Gunter Brumm parachutes silently through the sulphuric haze in the smoldering ruins of Berlin, past the Soviet troops that encircle the skeleton that the city has become in April 1945. With the precision and skill that has marked his brilliant military career, Brumm has completed the first stage of a simple yet seemingly impossible mission: to evade the Allied forces swarming over Europe and to smuggle Herr Wolf, the greatest war criminal of the twentieth century, to safety. Less than twenty-four hours later a special Russian team snakes its way into Berlin's city limits, headed for the Reich Chancellery. It is led by Vasily Petrov, the Berkut -named after the Russian eagles trained to hunt wolves, a man handpicked by Stalin himself for his ability to track down his quarry and driven by the knowledge that failure means certain death.